TEMATOLOGI: PEMBACAAN TEORITIS TERHADAP SALAH SATU METODE PENELITIAN SASTRA BANDING CLAUDIO GUILLEN - Lusia Kristiasih Dwi Purnomosasi (POETIKA, 2013)
Comparative literature study by Claudio Guillen has basic reason namely Weltliteratur. Guillen did criticism upon it to formulate his own method on comparative literature research. Goethe has inspired him to create the basic assumsion of  his theory; the one and the many and the universal and the local as well, upon which the internationality by socio-historical perspectives is conducted to identify the diachronic structure. It will reveal the supranationality within the primary data being compared. A researcher will stand on 5 principles, one of  which is thematology where a principle motif  of  a theme lies as a means of  dialog in internationality.Keywords: comparative literature, internationality, diachronic structure, supranationality